Carbamate derivatives and sesquiterpenoids from the South China Sea gorgonian Melitodes squamata - Li-Si Huang; Fei He; Hui Huang; Xiao-Yong Zhang; Shu-Hua Qi (Beilstein Journal of Organic Chemistry, 2012)
Five carbamate derivatives, obtucarbamates C and D (1, 2), dimethyl ((carbonylbis(azanediyl))bis(2-methyl-5,1-phenylene))dicarbamate (3), obtucarbamates A and B (4, 5), and four aromadendrane-type sesquiterpenoids, (+)-4β-N-methenetauryl-10β-methoxy-1β,5α,6β,7β-aromadendrane (6), (−)-4β-N-methenetauryl-10β-methoxy-1β,5β,6α,7α-aromadendrane (7), (−)-4α,10β-aromadendranediol (8), (+)-4β,10β-aromadendranediol (9) were obtained from the South China Sea gorgonian coral Melitodes squamata Nutting. Compounds 1, 2, 6, and 7 were new, and their structures were established by spectroscopic analyses. Compounds 6 and 7 contained a taurine group that was rarely found in marine natural compounds, and 7 showed moderate antibacterial activity. The possible biosynthesis routes of 1–5 were conjectured.